2019
DOI: 10.1016/j.devcel.2018.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of Myosin II Refines Tissue Material Properties to Buffer Mechanical Stress

Abstract: SummaryAs tissues develop, they are subjected to a variety of mechanical forces. Some of these forces are instrumental in the development of tissues, while others can result in tissue damage. Despite our extensive understanding of force-guided morphogenesis, we have only a limited understanding of how tissues prevent further morphogenesis once the shape is determined after development. Here, through the development of a tissue-stretching device, we uncover a mechanosensitive pathway that regulates tissue respo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 63 publications
7
70
0
Order By: Relevance
“…Previous studies suggested that tissue viscoelasticity influences the length scale of mechanical signal propagation, such as cortical flows in C. elegans zygotes (Mayer et al, 2010), or stress-induced cell shape change propagation across the Drosophila wing imaginal disc epithelium (Duda et al, 2019). Previous studies suggested that tissue viscoelasticity influences the length scale of mechanical signal propagation, such as cortical flows in C. elegans zygotes (Mayer et al, 2010), or stress-induced cell shape change propagation across the Drosophila wing imaginal disc epithelium (Duda et al, 2019).…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies suggested that tissue viscoelasticity influences the length scale of mechanical signal propagation, such as cortical flows in C. elegans zygotes (Mayer et al, 2010), or stress-induced cell shape change propagation across the Drosophila wing imaginal disc epithelium (Duda et al, 2019). Previous studies suggested that tissue viscoelasticity influences the length scale of mechanical signal propagation, such as cortical flows in C. elegans zygotes (Mayer et al, 2010), or stress-induced cell shape change propagation across the Drosophila wing imaginal disc epithelium (Duda et al, 2019).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Another so far largely unexplored question is whether tissue rheological properties are not only controlled by mechanochemical signalling but also affect such signalling. Previous studies suggested that tissue viscoelasticity influences the length scale of mechanical signal propagation, such as cortical flows in C. elegans zygotes (Mayer et al, 2010), or stress-induced cell shape change propagation across the Drosophila wing imaginal disc epithelium (Duda et al, 2019). However, whether and how tissues displaying nonuniform rheology affect the transduction of long-range mechanical signals generated by, e.g., supra-cellular actomyosin cables (Behrndt et al, 2012;Röper, 2013;preprint: Saadaoui et al, 2018;Shook et al, 2018) remains unclear.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…(9)] and thresholded tension remodelling [Eq. (10)] is sufficient to capture the experimentally observed mechanical behaviour of epithelial junctions, as well as ratcheted contractions upon episodic activation of contractility. In agreement with experimental data (Fig 2d), the junction shrinks to ∼ 80% of its initial length after the first contraction, while after the second contraction pulse, the normalised junction length is 70%, roughly 85% of its length after the first pulse (Fig 4c).…”
Section: A Ratchet-like Contractionsmentioning
confidence: 99%
“…A number of different experimental techniques and model systems have been used to probe the viscoelastic properties of epithelial cells. Rheological studies on suspended epithelial monolayers [8] have shown that stress dissipation in strained tissues is controlled by cell divisions, or actomyosin turnover [9,10]. Optical tweezers have been used to probe the mechanical response of cell-cell junctions under short time scale forces, where they respond elastically [6].…”
Section: Introductionmentioning
confidence: 99%